Компьютерная обработка изображений, полученных при помощи сенсора на базе гетероперехода CdS–Cu2S - Borschak, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
There has been created a multipurpose program that allows to manage the image sensor scanning, to process data to compensate for the heterogeneity of the sensor photosensitivity and convert the video data file into any format, accessible to standard programs, which process images.